Introduction: Science, Technology, Medicine – and the State: The Science-State Nexus in Scandinavia, 1850–1980. Issue 2 (29th April 2014) - Asdal, Kristin; Gradmann, Christoph; Gradmann, Christoph; Asdal, Kristin
<x content-type="archive" xml:space="preserve">Abstract</x> One of the common characteristics of science, technology, and medicine is their ambition to epistemologically and organizationally move beyond the confines of nation states. In practice, however, they develop differently in countries or regions. Scientists, engineers, and physicians are constrained as well as enabled by national boundaries and specific cultures. The cultural status of such practices in reverse is influenced by a country's history, politics, and the view of the role of science, technology, and medicine in society. It is the relation between a specific region, Scandinavia, and the history of science, technology, and medicine within this region that this issue of Science in Context sets out to explore. But what is this "Scandinavia"? To many, Scandinavia besides being a specific geographical region of three countries (Denmark, Sweden, and Norway) with entwined histories and closely related languages is a way of denoting a specific style or movement. "Scandinavian design" is renowned for three interrelated features; minimalism or simplicity, functionalism, and "design to the people" i.e. functional products for the average citizen (Beer 1975; Glambek 1997; Fallan 2012).